Sound Absorption Performance of Oil Palm Empty Fruit Bunch Fibreboards using different Fibre Lengths - Raman, Kokilla Vani; Samsudin, Dr. Emedya Murniwaty (Recent Trends in Civil Engineering and Built Environment, 2021)
Solid biomass wastes from oil palm industry have lots of benefits economically. Natural fibre wastes such as Oil Palm Empty Fruit Bunch (OPEFB) is suitable to use as sound absorber material in producing cement board since it contains chemical composition such as Holocellulose, Alpha cellulose, Pentosans, water, ash, and lignin that can improve the acoustic efficiency of the material compared to synthetic fibres. EFB was chosen as the main material since the increase in waste output creates environmental sustainability problems in terms of waste management and greenhouse gas emissions from solid biomass and POME. This study aims to utilize OPEFB as a raw fibre in cement board production and measure sound absorption coefficient (SAC) using different fiber lengths retained sieve (1mm, 3mm and 5 mm). and Raw fibers will undergo sodium hydroxide pretreatment to removed excessive oil content, unwanted dirt, lignin, and hemicellulose since it’s a cement retarded. The sound absorption coefficients (SAC) of OPEFB fiberboard were determined using impedance tube test by Transfer-Function Method according to BS EN ISO 10534-2: 2001. Further analysis has been done on the SAC values at 5-centre 1/3 octave frequencies to determine the Noise Reduction Coefficient (NRC). The relationship between fibre length and sound absorption performance of OPEFB fiberboard was established using correlations between the two parameters (fibre length and NRC). The finding is that the long fibre retained sieve 5mm is suitable to be used as it obtained optimum SAC value at 1000Hz and NRC value of 0.62 because long fibres would not fill the gaps or pores between the fibres such as dust particles and affect the sound absorption coefficient value. Thus, EFB can be used as a green technology product for revolutionary absorption for its promising future.